Membangun Smart Aparatur Sipil Negara (ASN) Menuju Birokrasi Berkelas Dunia Tahun 2024 - Hasan, Erliana (Jurnal Wahana Bina Pemerintahan, 2017)
From the presentation of the research focus data and the results of the discussion that have eem conducted, the following conclusions can be drawn, namely: ASN must have a sense of nationalism and implement general principles of good governance. In addition, a supporting factor in developing apparatus resources is needed, as ASN can formulate vision and values that can redesign work so that ASN conduct selection and assessment in conducting placements in accordance with the implementation of perfomance management systems. Then minimizing the innhibiting factor is where the apparatus does not keep up with the development of sciene and technology as well as the miss communication between ASN employees which hinders the running of efeective and efficient performance.